Alternative polyadenylation expands the mRNA isoform repertoire of human CD46 - Ly, Phuong Thao (2017)
Alternative polyadenylation is a prevalent mechanism regulating mammalian gene expression. While tandem 3′-Untranslated-Region (3′UTR) polyadenylation changes expression levels, Intronic PolyAdenylation generates shorter transcripts encoding truncated proteins. Intronic PolyAdenylation regulates 20% of genes and is especially common in receptor tyrosine-kinase transcripts, generating soluble repressors. Here we report that human CD46, encoding a TransMembrane repressor of complement and T-cell co-stimulator, expresses multiple isoforms by alternative polyadenylation. We provide evidence for polyadenylation at several introns by RT-PCR of 5′ intronic fragments, and by increase in such isoforms via functional U1 knockdown. We mapped various Intronic PolyAdenylation Sites by 3′ Rapid Amplification of cDNA Ends (3′RACE), which could generate soluble or membrane-bound but tail-less CD46. Intronic PolyAdenylation could add to the source of soluble CD46 isoforms in fluids and tissues, which increase in cancers and autoimmune syndromes. Furthermore, 3′RACE identified three PolyAdenylation Sites within the last intron and exon, whose transcripts with shortened 3′UTRs could support higher CD46 expression. Finally, 3′RACE revealed that the CD46 Pseudogene only expresses short transcripts by early polyadenylation in intron 2. Overall, we report a wide variety of CD46 mRNA isoforms which could generate new protein isoforms, adding to the diverse physiological and pathological roles of CD46.